Primary Lumbarspinal Paraganglioma: A Case Report With Literature Review of Last 10 Years. Issue 3 (August 2016) - Yaldiz, Can; Ceylan, Davut; Kaçira, Tibet; Kaçira, Özlem Kitiki; Kahyaoğlu, Zeynep
Abstract : Spinal paragangliomas are the neuroendocrine tumors of the extra-adrenal paraganglionic system. Spinal paragangliomas are very rare. A 64-year-old female patient admitted to our clinic with non-specific complaints. Intradural mass excision and lumbar posterior stabilization were performed with the diagnoses of degenerative narrow canal and intradural mass at L3 level following after the examinations. The pathological diagnosis came out as a paraganglioma. Full body scan images showed no multiple paragangliomas at any other location. Spinal paragangliomas are difficult to diagnose preoperatively due to the absence of any specific radiological and clinical findings and its very rare occurrence. We chose to present this case because of its formation in lumbar spinal canal, an unusual location for paragangliomas.